PERAN COMMUNITY-BASED LEARNING DALAM MENINGKATKAN PARTISIPASI SOSIAL MAHASISWA PADA KOMUNITAS PLURAL DAN INDIGENOUS : SYSTEMATIC LITERATURE REVIEW - Ni Wayan Rahayu Pradnyawati Putri; I Ketut Andika Pradnyana (WASIS : Jurnal Ilmiah Pendidikan, 2026)
Purpose: This study aims to analyze the role of Community-Based Learning (CBL) in enhancing university students’ social participation through a systematic synthesis of research findings. Design/methodology/approach: This research employed a Systematic Literature Review (SLR) using PRISMA 2020 guidelines to identify, screen, and evaluate relevant studies published between 2020 and 2025. Fifteen Indonesian research articles that discuss CBL, experiential learning, and student social engagement were analyzed qualitatively. Findings: The review shows that CBL effectively strengthens students’ social participation through authentic experiential learning, collaborative community interactions, and reflective processes that enhance communication, empathy, social awareness, and professional readiness. CBL also generates positive community impacts in areas such as literacy, health, and socio-economic empowerment. The review further identifies several implementation challenges, including limited time, community resistance, and insufficient institutional support. The findings conclude that successful CBL requires systematic curricular integration, continuous facilitator training, and sustainable partnerships between higher education institutions and communities.